2001
DOI: 10.1042/bj3580747
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, gene organization and expression of rainbow trout (Oncorhynchus mykiss) inducible nitric oxide synthase (iNOS) gene

Abstract: A full-length inducible nitric oxide synthase (iNOS ) gene has been sequenced for the first time outside the mammals, and the gene organization compared with that already determined for human iNOS. While there are some differences from the human gene, overall the exons show remarkable conservation in sequence and organization. As in human, the trout iNOS gene has 27 exons, with 18 of the trout exons being identical in size with the equivalent human exons. The cofactor-binding domains are found in the same exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…Thus, midintestine might have a high level of cellular and humoral effector of the immune response in S. paramamosain. Changing expression of NOS was found after pathogens stimulation in some vertebrates [22,23,31]. In the present study, the induction of NOS transcripts, detected by real-time qRT-PCR, was observed in midintestine, hepatopancrease and hemocytes in S. paramamosain after stimulation of LPS, poly I:C and V. parahaemolyticus (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, midintestine might have a high level of cellular and humoral effector of the immune response in S. paramamosain. Changing expression of NOS was found after pathogens stimulation in some vertebrates [22,23,31]. In the present study, the induction of NOS transcripts, detected by real-time qRT-PCR, was observed in midintestine, hepatopancrease and hemocytes in S. paramamosain after stimulation of LPS, poly I:C and V. parahaemolyticus (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…This structure is similar to those of NOS from vertebrates [11,14,15] and invertebrates [17,21,35] The motif prediction demonstrated that Heme, H4, Calmodulin, FMN, FAD (ADP), FAD (Flavin), FAD (Ribose), NADPH (Ribose), NADPH (ADP) and NADPH in the three types NOS showed high identity in LvNOS, suggesting that the function of NOS is conservative and LvNOS may have multi-functions. Five ATTTA motifs were found in the 3 0 UTR of LvNOS.…”
Section: Discussionmentioning
confidence: 57%
“…The third NOS isoform, inducible NOS (iNOS), is not typically expressed in resting cells and must first be induced by infection or pathogens [2]. In recent years, the three types of NOSs have been obtained and studied from many vertebrate species including nNOS from humans [3,4], mice [5], and fish [6]; eNOS from humans [7] cows [8], mice [9], and pigs [10]; and iNOS from mice [11e13], humans [2], and fish [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In bony fishes, NOS2 protein has been detected (Shin et al, 2000) and genes encoding nos2 homologs have been cloned in goldfish, Carassius auratus (Laing et al, 1996), rainbow trout, Oncorhynchus mykiss (Wang et al, 2001) and carp, Cyprinus carpio (Saeij et al, 2000). NOS2 has also been identified in a cartilaginous fish, the small spotted catshark, Scyliorhinus canicula (Reddick et al, 2006).…”
Section: Introductionmentioning
confidence: 97%